THE INVISIBLE PLAYERS: EXAMINING GENDER DYNAMICS IN ARMED CONFLICT IN NIGERIA - Shahid , Jennifer Iheanacho; Abwami, Innocent Michael (The Gender Truth Journal, 2024)
This paper explored the gender role dynamics in armed conflicts in Nigeria, with a focus on the roles women play in the Boko Haram insurgency. Contrary to the conventional view that women are merely victims of conflict, this study reveals that they are active participants, engaged in various roles such as logistics, intelligence gathering, and direct combat. Through quantitative analysis, it is evident that women’s involvement is influenced by a combination of economic necessity, ideological commitment, and coercion. The findings show significant regional differences, with women in the Northeast more involved in combat and intelligence roles, while those in the Northwest are primarily engaged in logistical support and smuggling. The study also highlights the profound challenges these women face during post-conflict reintegration, including stigma, economic hardship, and mental health issues. The paper argues that addressing these challenges requires targeted reintegration programmes, stigma reduction campaigns, and gender-sensitive legal and security frameworks. Additionally, the study challenges the notion that crime is gender-specific, demonstrating that both men and women play complementary roles in sustaining armed conflicts. The paper concludes with recommendations for community-based reintegration initiatives, mental health support, and further research to deepen our understanding of the evolving roles of women in armed conflicts.